2017
DOI: 10.1007/s13205-017-1020-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi level statistical optimization of l-asparaginase from Bacillus subtilis VUVD001

Abstract: Physical and chemical factors influencing the anti-leukemic l-asparaginase enzyme production by were optimized using multi-stage optimization on the basis of preliminary experimental outcomes obtained by conventional one-factor-at-a-time approach using shake flasks. Process variables namely carbon, nitrogen sources, pH and temperature were taken into consideration during response surface methodology (RSM) optimization. The finest enzyme activity of 0.51 IUml obtained by OFAT method was enhanced by 3.2 folds us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
1
0
3
Order By: Relevance
“…Figure 5 indicated that pH 7.0 (142.71 U/mg) support maximal enzyme production, although it could produce invariably considerable level of enzyme over a wide range of pH between 4.0 (48.69 U/mg)and pH 11.0 (39.12 U/mg). These observations also suggest that this bacterial strain have a wide range of pH.Jiaet al (2013) reported that the optimum pH was 7.5 from B. subtilis B11−06 while Erva (2018) showedthat theoptimum pH was 8.3.…”
Section: Effect Of Different Inoculum Size On Lasparaginase Productionmentioning
confidence: 73%
“…Figure 5 indicated that pH 7.0 (142.71 U/mg) support maximal enzyme production, although it could produce invariably considerable level of enzyme over a wide range of pH between 4.0 (48.69 U/mg)and pH 11.0 (39.12 U/mg). These observations also suggest that this bacterial strain have a wide range of pH.Jiaet al (2013) reported that the optimum pH was 7.5 from B. subtilis B11−06 while Erva (2018) showedthat theoptimum pH was 8.3.…”
Section: Effect Of Different Inoculum Size On Lasparaginase Productionmentioning
confidence: 73%
“…5). En otros casos, B. subtilis VUVD001 mejoró su producción hasta 2.88 U/mL (3.2 veces) a pH 7.56 (Erva et al 2018), y B. licheniformis PPD37 halotolerante incrementó seis veces su producción a pH 7.5 en medio M9 (Patel et al 2021).…”
Section: Resultados Y Discusiónunclassified
“…La L-asparaginasa es producida por microorganismos, vegetales y animales, siendo los primeros la fuente más importante debido a su rápida producción, además de permitir una eficiente purificación de la enzima y su escalamiento (Cachumba et al 2016). Entre los microorganismos utilizados en la producción de L-asparaginasa se encuentran los Streptomyces, Bacillus, Lysinibacillus, Staphylococcus, Rouxiella, Erwinia, Escherichia, Acinetobacter, Pseudomonas (Erva et al 2018;Arévalo-Tristancho et al 2019;Gilavand et al 2019;Prihanto et al 2019;Setiawan & Larasati 2019). Sin embargo, para lograr altos niveles de producción se requiere buena estabilidad en condiciones extremas, como la que han demostrado bacterias que mantienen actividad con alta eficiencia y termoestabilidad (Zuo et al 2015).…”
Section: Introductionunclassified
“…Inicialmente, foram propostas modificações químicas como forma de ocultar epítopos expostos na estrutura proteica dessa enzima, imunologicamente ativos e capazes de estimular as reações de hipersensibilidade (NARTA et al, 2007). A proposta mais conhecida nesse sentido resultou no desenvolvimento da forma peguilada da enzima (ABUCHOWSKI et al, 1979 Bacillus (ALRUMMAN et al, 2019;ERVA et al, 2018;GHOLAMIAN et al, 2013;HYMAVATHI et al, 2010); Pseudomonas aeruginosa (GECKIL et al, 2006) Portanto, ainda há muito a ser explorado entre as leveduras que, por serem organismos eucarióticos e apresentarem as vantagens já citadas anteriormente em relação a sistemas procarióticos, apresentam grande perspectiva de uso para a produção de biofármacos, como a L-ASNase. Dessa forma, a pesquisa desses microrganismos em diversos nichos traz uma perspectiva para encontrar uma L-ASNase com ação antileucêmica e, ao mesmo tempo, menos imunogênica que as congêneres disponíveis no mercado.…”
Section: Em Busca De Alternativas àS L-asnases Convencionaisunclassified